Effects of Cu–K Co‐Doping on the Morphological, Optical, and Electrical Properties of NiO Films Deposited by Spin‐Coating Sol–Gel Method. Issue 5 (29th January 2020) - Song, Meng-Si; Liu, Chao-Qian; Wang, Nan; Lun, Ting-Ting; Zhai, Xiao-Na; Ge, Qing; Zhang, Xiao-Yang
Abstract : Cu–K co‐doped NiO films (Ni1–2 x Cu x K x O and x  = 0–0.05) are deposited on common glass substrates by the spin‐coating sol–gel method. The phase and the morphological, optical, and electrical properties of NiO films as a function of the Cu–K co‐doping concentration are explored by X‐ray diffraction, scanning electron microscopy, and ultraviolet–visible spectrophotometer and Hall effect measurement systems, respectively. All the films are pure phases of the cubic rock‐salt structure. As the doping concentration increases, the preferred orientation of the Ni1–2 x Cu x K x O films changes from (200) to (111). Moreover, the surface morphologies of the films are obviously affected by the Cu–K co‐doping concentration. The absorption coefficients of the Cu–K co‐doped NiO films are relatively higher than that of the undoped film on the whole in the visible region except x  = 0.02. With the increase in doping concentration, the resistivity of the films decreases on the whole. Finally, the figures of merit (FOM) of the films are considered, and the maximum FOM of the films is achieved at x  = 0.02. Abstract : The preferred orientation of Ni1–2 x Cu x K x O films changes from (200) to (111) with increasing doping concentration. The surface of the films with x  = 0.4 and 0.5 presents some circular bulge, and some bulges are broken at their top for x  = 0.05. It is found that the Ni0.96 Cu0.02 K0.02 O film has a better balance between transmission and sheet resistance.